Impasses of the Post-Global: Theory in the Era of Climate Change, Vol. 2 - Sussman, Henry (Critical Climate Change, 2012)
The diverse materials comprising Impasses of the Post-Global take as their starting point an interrelated, if seemingly endless sequence of current ecological, demographic, socio-political, economic, and informational disasters. These include the contemporary discourses of deconstruction, climate change, ecological imbalance and despoilment, sustainability, security, economic bailout, auto-immunity, and globalization itself. With essays by James H. Bunn, Rey Chow, Bruce Clarke, Tom Cohen, Randy Martin, Yates McKee, Alberto Moreiras, Haun Saussy, Tian Song, Henry Sussman, Samuel Weber, Ewa P. Ziarek, and Kryzsztof Ziarek.